Does modified Blumgart anastomosis without intra-pancreatic ductal stenting reduce post-operative pancreatic fistula after pancreaticojejunostomy? - Sohei Satoi (Asian Journal of Surgery, 2019)
Summary: Background: Post-operative pancreatic fistula (POPF) is one of the most common and serious complications after pancreaticoduodenectomy (PD). The aim of this study is to retrospectively compare clinically relevant (CR) POPF and other complications after pacreaticojejunostomy (PJ) after modified Kakita (m-Kakita) or modified Blumgart (m-Blumgart) anastomoses without stenting in a single institution. Methods: One hundred twenty-eight patients underwent PJ using m-Kakita anastomoses (two interrupted penetrating sutures) between January 2009 and December 2011. One hundred eighteen patients underwent m-Blumgart anastomoses (two transpancreatic/jejunal seromuscular sutures to cover the pancreatic stump with jejunal serosa) between January 2014 and December 2015. Demographics, clinical characteristics, and post-operative mortality and morbidity were retrospectively compared between the two groups. Results: There were no significant differences in demographics or clinical characteristics between the two groups except operative time. A significantly lower rate of CR-POPF was found in the m-Blumgart group relative to the m-Kakita group (10% vs. 19%, p = 0.038). Univariate and multivariate analyses revealed that the m-Blumgart anastomosis and fistula risk category (Negligible, Low) were independently protective against CR-POPF (p < 0.05). Conclusion: This retrospective single-center study demonstrated that the modified Blumgart method without pancreatic duct stenting was associated with a lower rate of CR-POPF. Keywords: Clinically relevant pancreatic fistula, Pancreaticoduodenectomy, Blumgart anastomosis, Morbidity, Mortality